The Use of Youtube as a Learning Tool in Teaching Listening Skill - Pratama, Shadam Hussaeni Handi; Arifin, Riyadh Ahsanul; Widianingsih, Ayang Winda Sri (iora, 2020)
YouTube is not only a platform that individuals share, upload, comment on videos; but also teachers and educators can make practical and effective use of it to the best as great that students can have more an advantage or profit gained. This study aims to carry out a systematic or formal inquiry to discover and examine the facts of how active and distinguished YouTube can be in the educational process and how it is beneficial for language teachers to enhance the skills of students. The study exhibits different theoretical frameworks that equip the employment of technology to increase the learning/teaching process. In using multimedia, video clips used to develop teachers’ abilities for using technology in classrooms. The objectives of this research are to give knowledgeably and clear explanations about teaching students’ listening skills through English video. The researcher emerges a questionnaire and applies it to third-semester of college students, Ma’soem University to give confirmation and show the advantages of technology in the academic field. The paper investigates classes where computers can be utilized, and also appear the defiance that faces teachers and educators regarding this application. The researchers terminated that YouTube is a necessary tool in classrooms as it appeals to the attention of students and envolves their mentality and creativity. It also assists cover the materials exhaustive, especially language. YouTube leads the fun element into classes, through meet the interests of students. Equivalent findings have a remarkable impact on the learning process as the students will realize the educational environment more uplift and inspire. Besides, they notice the material presented worth studying, and this method, they would admire the attempt expend in explaining the information. The research aspires to be of worth to teachers for the operation of technology and students to have a superior apprehension of the materials extend.